Alcohol Use and Breast Cancer: A Critical Review. (30th April 2016) - Shield, Kevin D.; Soerjomataram, Isabelle; Rehm, Jürgen
Abstract : The objective of this study was to outline the biological pathways of alcohol‐attributable breast cancer, the epidemiological risk relationship between alcohol consumption and breast cancer, and the global burden of breast cancer incidence and mortality attributable to alcohol consumption, with a focus on light drinking. First, the literature regarding the biological mechanisms of how alcohol affects the risk of breast cancer was reviewed and summarized. Second, a search of meta‐analyses that evaluated the risk relationship between alcohol consumption and breast cancer was conducted. Last, the burden of alcohol‐attributable breast cancer incidence and mortality was estimated by means of a Population‐Attributable Fraction methodology. Data on alcohol consumption were obtained from the Global Information System on Alcohol and Health, and data on cancer incidence and mortality were obtained from the GLOBOCAN database. Alcohol consumption affects breast cancer risk through the alteration in hormone levels and the associated biological pathways, the metabolism of ethanol resulting in carcinogens, and the inhibition of the one carbon metabolism pathway. The systematic review found 15 meta‐analyses on the risk relationship between alcohol consumption (also light consumption) and the risk of breast cancer. All but 2 of these analyses showed a dose–response relationship between alcohol consumption and the risk of breast cancer. An estimated 144, 000 (95% confidence interval [CI]: 88, 000 to 200, 000) breast cancer cases and 38, 000 (95% CI: 2, 400 to 53, 000) breast cancer deaths globally in 2012 were attributable to alcohol, with 18.8% of these cases and 17.5% of these deaths affecting women who were light alcohol consumers. All levels of evidence showed a risk relationship between alcohol consumption and the risk of breast cancer, even at low levels of consumption. Due to this strong relationship, and to the amount of alcohol consumed globally, the incidence of and mortality from alcohol‐attributable breast cancer is large. Abstract : The global burden of breast cancer is large and growing, and, accordingly, there is a need for increased attention to breast cancer prevention. This review found that the biological pathways for alcohol‐associated breast carcinogenesis are multifold and that even light alcohol consumption is causally related to breast cancer. Furthermore, this review estimated that alcohol caused 144, 000 breast cancer cases and 38, 000 breast cancer deaths globally in 2012, with 18.8% of these cases and 17.5% of these deaths affecting light drinkers.